AtOMA1 Affects the OXPHOS System and Plant Growth in Contrast to Other Newly Identified ATP-Independent Proteases in Arabidopsis Mitochondria - Iwona Migdal (Frontiers in Plant Science, 2017)
Compared with yeast, our knowledge on members of the ATP-independent plant mitochondrial proteolytic machinery is rather poor. In the present study, using confocal microscopy and immunoblotting, we proved that homologs of yeast Oma1, Atp23, Imp1, Imp2, and Oct1 proteases are localized in Arabidopsis mitochondria. We characterized these components of the ATP-independent proteolytic system as well as the earlier identified protease, AtICP55, with an emphasis on their significance in plant growth and functionality in the OXPHOS system. A functional complementation assay demonstrated that out of all the analyzed proteases, only AtOMA1 and AtICP55 could substitute for a lack of their yeast counterparts. We did not observe any significant developmental or morphological changes in plants lacking the studied proteases, either under optimal growth conditions or after exposure to stress, with the only exception being retarded root growth in oma1-1, thus implying that the absence of a single mitochondrial ATP-independent protease is not critical for Arabidopsis growth and development. We did not find any evidence indicating a clear functional complementation of the missing protease by any other protease at the transcript or protein level. Studies on the impact of the analyzed proteases on mitochondrial bioenergetic function revealed that out of all the studied mutants, only oma1-1 showed differences in activities and amounts of OXPHOS proteins. Among all the OXPHOS disorders found in oma1-1, the complex V deficiency is distinctive because it is mainly associated with decreased catalytic activity and not correlated with complex abundance, which has been observed in the case of supercomplex I + III2 and complex I deficiencies. Altogether, our study indicates that despite the presence of highly conservative homologs, the mitochondrial ATP-independent proteolytic system is not functionally conserved in plants as compared with yeast. Our findings also highlight the importance of AtOMA1 in maintenance of proper function of the OXPHOS system as well as in growth and development of Arabidopsis thaliana.